Investigation of corrosion behavior of polypyrrole-coated Ti using dynamic electrochemical impedance spectroscopy (DEIS). Issue 83 (23rd August 2016) - Rikhari, Bhavana; Mani, S. Pugal; Rajendran, N.
Abstract : In the present work, dynamic electrochemical impedance spectroscopy (DEIS) was used to investigate the corrosion behavior of polypyrrole (PPy)-coated titanium (Ti) in simulated body fluid (SBF) solution. Abstract : In the present work, dynamic electrochemical impedance spectroscopy (DEIS) was used to investigate the corrosion behavior of polypyrrole (PPy)-coated titanium (Ti) in simulated body fluid (SBF) solution. The deposition of PPy on Ti was carried out using the cyclic voltammetry (CV) technique. The formation of the PPy coating was confirmed by infrared and Raman spectroscopy. Scanning electron microscopy (SEM) studies revealed the deposition of a 7 μm-thick PPy coating with a cauliflower-like morphology. The surface roughness and wettability of the coating were confirmed by atomic force microscopy (AFM) and water contact angle studies. The corrosion behavior of uncoated and PPy-coated Ti was investigated in SBF using DEIS and polarization studies. DEIS was carried out from the open circuit potential (OCP) to dissolution regions of the uncoated and PPy-coated Ti with a step potential of 0.5 V. The variation in the charge transfer resistance ( R ct ) value as a function of potential exhibited distinctive impedance behavior for the uncoated and coated substrates. The PPy-coated Ti showed a higher R ct at each potential thereby indicating the higher corrosion resistance of the coating. The highest polarization resistance ( R p ) and lowest corrosion current density ( i corr ) of PPy-coated Ti obtained from the potentiodynamic polarization studies revealed the enhanced corrosion resistance. The potentiostatic polarization studies for the PPy-coated substrate showed a low current density value at the OCP and dissolution potential and it can be attributed to the enhanced protection ability of the coating. Additional evidence in support of the enhanced corrosion protection performance of PPy was obtained from the Bode-phase angle maximum value at the OCP and dissolution potential.